Perbedaan pengetahuan, sikap, higiene personal dan cemaran mikroba di pondok pesantren kota dan desa - Febriyani Febriyani; Putri Ronitawati; Vitria Melani; Mertien Sa'pang; Lintang Purwara Dewanti (Darussalam Nutrition Journal, 2022)
Background: Healthy and clean food is the basic principle of institutional food administration. In the practice of organizing mass meals such as in Islamic boarding schools, the risk of food poisoning in students can be caused by various factors. These include lack of knowledge and sanitation hygiene, especially for food handlers. Objective: To determine differences in knowledge, attitudes, personal hygiene of food handlers, and microbial contamination in urban and rural Islamic boarding schools. Method: Used a cross-sectional design, with 13 respondents in urban Islamic boarding schools and 18 respondents in rural Islamic boarding schools. The data collection instruments include knowledge, attitude, personal hygiene, and food safety score (SKP) questionnaires. The germ numbers were tested using the total plate count (TPC) and most probable number (MPN) methods. Data analysis using Independent T-Test test. Results: The knowledge, attitudes, and personal hygiene of respondents in rural Islamic boarding schools were higher than those in urban boarding schools. Bivariate analysis showed that there was a significant difference in personal hygiene in the two groups of Islamic boarding schools (p=0,002). Conclusion: Food handlers have not fully implemented the principles of personal hygiene. It is necessary to conduct training and counseling for food handlers in Islamic boarding schools to improve the quality of the food produced for the students. AbstrakLatar Belakang: Penyediaan makanan yang sehat dan bersih merupakan prinsip dasar penyelenggaraan makanan institusi. Dalam praktik penyelenggaraan makanan massal seperti di pondok pesantren, risiko keracunan makanan pada siswa dapat disebabkan berbagai faktor. Diantaranya kurang pengetahuan dan penerapan higiene sanitasi khususnya pada penjamah makanan. Tujuan: Mengetahui perbedaan pengetahuan, sikap, personal higiene penjamah makanan dan cemaran mikroba di pondok pesantren kota dan desa. Metode: Rancangan cross-sectional, dengan 13 responden di pondok pesantren kota dan 18 responden di pondok pesantren desa. Instrumen pengumpulan data meliputi kuesioner pengetahuan, sikap, personal higiene, dan formulir skor keamanan pangan (SKP). Angka kuman diuji dengan metode total plate count (TPC) dan most probable number (MPN). Analisis data menggunakan uji T-Test Independent. Hasil: Pengetahuan, sikap, dan higiene personal responden di pondok pesantren desa lebih tinggi dibandingkan dengan pondok pesantren kota. Analisis bivariat menunjukkan tidak terdapat perbedaan yang signifikan pada pengetahuan (p= 0,417) dan sikap (p=0,089) di kedua kelompok pesantren. Terdapat perbedaan signifikan pada higiene personal di kedua kelompok pesantren (p=0,002). Simpulan: Penjamah makanan belum sepenuhnya menerapkan prinsip personal hygiene. Perlu dilakukan pelatihan dan penyuluhan bagi penjamah makanan di pondok pesantren untuk meningkatkan kualitas makanan yang dihasilkan untuk para santri.